The effect of living alone on the mental health of the economically active floating population during the COVID-19 pandemic - Xu, Junzhou; Zhang, Ling (Frontiers in Public Health, 2022)
Background The Coronavirus disease 2019 (COVID-19) pandemic broke out at the end of 2019 in China. Through a strict Zero-Tolerant strategy, the pandemic was nearly controlled in the first half of 2020, and production resumed in most regions of China. A survey was performed to explore the effect of living alone on the mental health of the economically active floating population (EAFP) in developed regions of China during the COVID-19 pandemic. Methods The online cross-sectional survey was conducted in work resumed time in the first half of 2020 in several developed regions of China. The 12-item General Health Questionnaire (GHQ-12) is used to assess the mental health status. The Multi-level ordinary least squares regression was performed on a total of 4,405 samples to examine the relationships between living alone and the participants' mental health. Results Many participants lived alone during the COVID 19 pandemic. Living alone is negatively associated with mental health (p < 0.01) for EAFP. The effect of living alone on mental health is stronger for females than males and for people with a lover than those without a lover. It is also stronger for the seniors (aged 56–70) than younger ones (aged 16–35), and has no significant influence on the middle-aged population (36–55). The effect is significant for self-employed people and employees, and is not significant for unemployed ones. Furthermore, the right amount of online entertainment can lower the effect of living alone on mental health. Conclusion The results show that living alone strongly affected the mental health of EAFP during the COVID 19 pandemic. Moreover, this effect has generated new inequalities among different groups. In addition, to provide more public services to support people against the pandemic, the government should provide more psychological support to those who live alone and guide them to establish a correct view of marriage and love to reduce living alone negative effect and prevent them from mental health problems.